Effect of Ashwagandharista (Withania somnifera) on the kidney functions of male and female rats - Rahman, Tasmina; Hasan, Md Rakib; Choudhuri, MSK (Jahangirnagar University Journal of Biological Sciences, 2019)
The key objective of this present study was to analyze the effect(s) of Ashwagandharishta on the kidney functions of both male and female Albino rats. Chronic toxicity tests were also done. Following treatments the rats were observed for 51 days to know the effects of Ashwagandharishta on kidney functions considering 3 parameters such as serum urea, creatinine and uric acid. Our results failed to exhibit a significant increase in serum urea level at low dose (P<0.01), medium dose (P<0.05) and at high dose (P<0.001) in male rat groups; but with female rat groups our results showed significant increase in serum urea level at three dose levels. Regarding serum creatinine level male rats and female rats showed a trend of increase in level at different dose but effects were insignificant except medium dose in male rats (P<0.05). Regarding serum uric acid level our results failed to show a significant increase irrespective of dose. Jahangirnagar University J. Biol. Sci. 8(1): 1-7, 2019 (June)